KONSTRUKSI SOSIAL BURUH DALAM HUBUNGAN INDUSTRIAL DAN PUBLIC RELATIONS: KASUS UNJUK RASA BURUH TEKSTIL DI KABUPATEN BANDUNG - Suwandi Sumartias (Indonesian Journal of Dialectics, 2011)
The  aim of the research  to create the model of social construction of textile labor about  Demonstration and view of labor relations that is expected.The method used is  qualitative method with phenomenology tradition.  The research subjects are  10 labor consist of 4 textile labor and 6  labor activists in  Kabupaten  Bandung, in  criteria that the informant have ever and always get  involved  in every demonstration. Through  depth interviews and observation, gained the informant ‘s statements  of experiences, comprehension, behavior and  communication meaning The research has been being carried out  since  2006. The result of the research  indicates that labor’s comprehension about demonstration is not only the secret and main weapon to  fight for their better fate. The labor realize that demonstration is important but it is not the only way to express of  their aspiration. Bipartite communication (labor-industrialist)  in form of  negotiation is better way. Demonstration is done  when  there is a deadlock  situation in  communication and negotiation between labor and industrialist. Demonstration  also happen  when the governments on the industrialist side or it ignore the labor’s need. Labor demonstration is   social link of a long history: Class politic; exploitation; domination of bourgeois; fight of practical interest, ideology and culture in productive relations. The reason of the textile labor demonstration is caused of wage system and  basic needs as human being, family and collective. Industrialist’s awareness of labor’s  life improvement is still low. Communication meaning  of demonstration: communication gap, exploitation, discrimination, pressure and powerlessness of labor.